Hubungan Bobot Lahir, Bobot Sapih dan Jenis Kelamin terhadap Paritas Sapi Simmental di BPTU HPT Padang Mengatas - Rica Mega Sari; Harissatria Harissatria; Mila Afriani (Jurnal Peternakan Mahaputra, 2020)
This study aims to determine the relationship between birth weight, weaning weight and sex on parity of Simmental cattle in BPTU HPT Padang Mengatas. The material of this research is data from 104 Simmental parity I, II and III cows kept in BPTU HPT Padang Mengatas. The method used in this research is a case study method and the sampling is done by purposive sampling. The data were obtained by looking at the Simmental cattle recording records in BPTU HPT Padang Mengatas. The variables observed were birth weight, weaning weight and sex as the independent variable and parity as the dependent variable. Data analysis used multiple linear regression with stepwise method and its processing used SPSS 22 for windows to find variables that were significantly related to parity. The results of this study indicate that the mean birth weight P1 = 34.94 kg; P2 = 43.11 kg; P3 = 45.93 kg. The average weaning weight P1 = 196.14 kg; P2 = 230.74 kg; P3 = 248.73 kg and the average gender P1 = 0.48; P2 = 0.52; P3 = 0.50. It can be concluded that birth weight, weaning weight and sex of Simmental cattle have a significant relationship to parity of Simmental cattle in BPTU HPT Padang Mengatas, because increased parity tends to increase birth weight and weaning weight of calves, calves with heavy birth weight tend to be male.